Reconfigurable low-emissivity optical coating using ultrathin phase change materials - Youngblood, N; Talagrand, C; Porter, BF; Galante, CG; Kneepkens, S; Triggs, G; Sarwat, SG; Yarmolich, D; Bonilla, RS; Hosseini, P; Taylor, RA; Bhaskaran, H (American Chemical Society, 2021)
A method for controlling the optical properties of a solid-state film over a broad wavelength range is highly desirable and could have significant commercial impact. One such application is smart glazing technology where near-infrared solar radiation is harvested in the winter and reflected it in the summer─an impossibility for materials with fixed thermal and optical properties. Here, we experimentally demonstrate the first spectrally tunable, low-emissivity coating using a chalcogenide-based phase-change material (Ge20Te80), which can modulate the solar heat gain of a window while maintaining neutral-coloration and constant transmission of light at visible wavelengths. We additionally demonstrate the controlled transfer of absorbed near-infrared energy to far-infrared radiation, which can be used to heat a building’s interior and show fast, sub-millisecond switching using transparent electrical heaters integrated on glass substrates. These combined properties result in a smart window that is efficient and aesthetically pleasing─crucial for successful adoption of green technology.